NUCLEIC ACIDS THAT SUPPRESS GENE EXPRESSION OF DISEASE-SPECIFIC COL3A1 MUTANT ALLELES AND PHARMACEUTICAL COMPOSITIONS FOR TREATING VASCULAR EHLERS-DANLOS SYNDROME - YOSHIDA TETSUO; HARA MITSUNOBU (2022)
To provide a pharmaceutical composition for use in treating diseases caused by mutations in collagen 3A1.SOLUTION: In a subject who has a gene encoding a variant of collagen 3A1 and a gene encoding a wild type thereof, respectively, a pharmaceutical composition is provided for treating a disease caused by the variant. The pharmaceutical composition comprises a nucleic acid selected from siRNA or shRNA. The variant is a gene encoding collagen 3A1 having a G to T substitution at the base corresponding to position 755 in the specific base sequence or a gene encoding collagen 3A1 having a G to A substitution at the base corresponding to position 547 in the specific base sequence. The nucleic acid can suppress the expression of the variant more strongly than the expression of the wild type.SELECTED DRAWING: None 【課題】コラーゲン３Ａ１の変異に起因する疾患を処置することに用いるための医薬組成物の提供。【解決手段】コラーゲン３Ａ１の変異型をコードする遺伝子と野生型をコードする遺伝子をそれぞれ有する対象において、当該変異型に起因する疾患を処置するための医薬組成物であって、ｓｉＲＮＡまたはｓｈＲＮＡから選択される核酸を含み、当該変異型が、特定の塩基配列における７５５番目に対応する塩基のＧからＴへの置換を有するコラーゲン３Ａ１をコードする遺伝子であるか、または前記特定の塩基配列における５４７番目に対応する塩基のＧからＡへの置換を有するコラーゲン３Ａ１をコードする遺伝子であり、前記核酸が、野生型の発現よりも前記変異型の発現を強く抑制することができる、医薬組成物。【選択図】なし